Luther's Theology of the Cross Fifteen Years after Heidelberg: Lectures on the Psalms of Ascent - Kolb, Robert (The journal of ecclesiastical history, 2010)
Luther's hermeneutical principles labelled ‘the theology of the cross’, developed in his ‘Heidelberg theses’ of 1518, continued to guide his formulation of biblical teaching throughout his career. In lectures on the Psalms of ascent (1532–3), under quite different circumstances, Luther claimed again that ‘Our theology is a theology of the cross’. Five elements of his Heidelberg theologia crucis guided his interpretation in these lectures. The distinction of the hidden and the revealed God, the focus on Christ's atoning sacrifice for sin, the reliance on faith in God's Word rather than human reason, God's working ‘under the appearance of opposites’ and the suffering involved in battling Satan shape his treatment of many passages in the lectures on Psalms cxx–cxxxiv.